2012
DOI: 10.1194/jlr.m023689
|View full text |Cite
|
Sign up to set email alerts
|

Surprising unreactivity of cholesterol-5,6-epoxides towards nucleophiles

Abstract: This article is available online at http://www.jlr.org thesis ( 2 ). We showed that ChEH was fully inhibited by therapeutic doses of AEBS ligands, including drugs belonging to different pharmacological classes and widely used nutritional compounds. These compounds include tamoxifen (tam), one of the main drugs used for the fi rstline and long-term hormone therapy of breast cancers; raloxifene, which has been approved for the prevention of osteoporosis ( 3 ); amiodarone, which is widely used for the prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 39 publications
3
30
0
Order By: Relevance
“…Surprisingly, the molecular entity responsible for the ChEH activity was in fact the antiestrogen binding site, a multidomain protein that has high affinity for the pharmaceutical tamoxifen, which is composed of two enzymes, For years, it had been believed that 5,6-cholesterol epoxides had a role in carcinogenesis (Petrakis, 1986;Poirot and Silvente-Poirot, 2013). Although early studies indicated that 5,6-cholesterol epoxide binds covalently to nucleophilic DNA (Blackburn et al, 1979;Sevanian and Peterson, 1984), 5,6-cholesterol epoxide is relatively unreactive with nucleophiles, only forming adducts with mercaptoethanol and aminoethanol under catalytic conditions (Paillasse et al, 2012). Despite this lack of chemical reactivity, an undescribed enzyme was found to catalyze the addition of histamine to 5,6a-cholesterol epoxide, resulting in Dendrogenin A (DDA).…”
Section: A History Of Epoxide Hydrolasesmentioning
confidence: 99%
“…Surprisingly, the molecular entity responsible for the ChEH activity was in fact the antiestrogen binding site, a multidomain protein that has high affinity for the pharmaceutical tamoxifen, which is composed of two enzymes, For years, it had been believed that 5,6-cholesterol epoxides had a role in carcinogenesis (Petrakis, 1986;Poirot and Silvente-Poirot, 2013). Although early studies indicated that 5,6-cholesterol epoxide binds covalently to nucleophilic DNA (Blackburn et al, 1979;Sevanian and Peterson, 1984), 5,6-cholesterol epoxide is relatively unreactive with nucleophiles, only forming adducts with mercaptoethanol and aminoethanol under catalytic conditions (Paillasse et al, 2012). Despite this lack of chemical reactivity, an undescribed enzyme was found to catalyze the addition of histamine to 5,6a-cholesterol epoxide, resulting in Dendrogenin A (DDA).…”
Section: A History Of Epoxide Hydrolasesmentioning
confidence: 99%
“…One peculiarity of epoxide-bearing substances is their instability due to the high reactivity of the epoxide ring towards nucleophiles including amines, thiols and hydroxyl groups that are found in bio-macromolecules and biological media1314. Surprisingly, 5,6-ECs were found to be different from other epoxide-bearing substances in that they do not react spontaneously with nucleophiles, including amines, thus making 5,6-ECs extremely stable in biological media1115.…”
mentioning
confidence: 99%
“…This hypothesis was chemically tested but no reactions occurred between 5,6a-EC or 5,6b-EC and nucleophiles containing amine or thiol groups, establishing a surprising non-spontaneous reactivity of 5,6-EC towards nucleophiles [37,38]. In the presence of a catalyst (heat or a Lewis acid), a conjugation reaction did take place but only between 5,6a-EC and nucleophiles, with 5,6b-EC remaining totally unreactive under the conditions tested [37,38]. Interestingly, while three different substitution products at the C6 were possible [10], only one was obtained, with a 6b substitute product resulting from the trans diaxial ring opening of the epoxide by the primary (a) amine of HA.…”
Section: The Aebs Has Cholesterol-56-epoxide Hydrolase Activitymentioning
confidence: 98%